2020
DOI: 10.1371/journal.pone.0226341
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of forest cover and carbon stock changes in sub-tropical pine forest of Azad Jammu & Kashmir (AJK), Pakistan using multi-temporal Landsat satellite data and field inventory

Abstract: This study aimed at estimating temporal (1989-2018) change in forest cover, carbon stock and trend in corresponding CO 2 emissions/sequestration of a subtropical pine forest (STPF) in AJK, Pakistan. Our field inventory estimation shows an average above ground biomass (AAGB) accumulation of 0.145 Kt/ha with average carbon stock (ACS) value of 0.072 Kt/ha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
(51 reference statements)
2
9
0
Order By: Relevance
“…The total forest area in the entire district was calculated as 63 km 2 using the GFW data set for 2019. The study by Khan et al [92] used Landsat TM, Landsat ETM+, and Landsat OLI satellite data sets to map temperate forests in Sudhnuti district (471 km 2 area), AJK. They extracted vegetation fractions (forest, non-forest area) using Linear Spectral Mixture Analysis (LSMA), a supervised image classification approach, for 1989, 1993, 1999, 2005, 2010, 2015, and 2018.…”
Section: Other Districtsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total forest area in the entire district was calculated as 63 km 2 using the GFW data set for 2019. The study by Khan et al [92] used Landsat TM, Landsat ETM+, and Landsat OLI satellite data sets to map temperate forests in Sudhnuti district (471 km 2 area), AJK. They extracted vegetation fractions (forest, non-forest area) using Linear Spectral Mixture Analysis (LSMA), a supervised image classification approach, for 1989, 1993, 1999, 2005, 2010, 2015, and 2018.…”
Section: Other Districtsmentioning
confidence: 99%
“…However, their study did not mention the achieved values. In the first study of 2020, Khan et al [92] used 140 validation points to map the forest and non-forest fractional maps. This study reported an overall accuracy of 96%, kappa value of 0.92, producer's accuracy of 97% for forest and 95% for the non-forest area, and user's accuracy of 96% for forest and 97% for the non-forest area.…”
Section: Accuracies Assessments and Validations For Forest Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, remote sensing techniques [1] are considered a powerful tool for analyzing land use. However, it is necessary to consider different techniques for analyzing satellite images from different historical and current periods of land use [8].…”
Section: Changes In Rural Areas Of the City Of Carazinho (Rs) Betweenmentioning
confidence: 99%
“…Forests cover approximately one-third of the earth's land surface area [1], and tropical and sub-tropical forests form a major component of the total area. Natural forests host diverse plant and animal species [2], caters to forage resources for insect pollinators [3], and help alleviate the effects of climate change by atmospheric carbon sequestration [4,5].…”
Section: Introductionmentioning
confidence: 99%